An in vitro platform for the enzymatic characterization of the rhomboid protease RHBDL4 - Bhaduri, Satarupa; Braza, Mac Kevin E; Stanchev, Stancho; Tauber, Marina; Al-Bawab, Raghad; Liu, Lawrence J; Trujillo, Diego F; Solorio-Kirpichyan, Kristina; Srivastava, Ambuj; Sanlley-Hernandez, Javier; O'Donoghue, Anthony J; Lemberg, Marius K; et al. (bioRxiv, 2024)
Rhomboid proteases are ubiquitous intramembrane serine proteases that can cleave transmembrane substrates within lipid bilayers. They exhibit many and diverse functions, such as but not limited to, growth factor signaling, immune and inflammatory response, protein quality control, and parasitic invasion. Human rhomboid protease RHBDL4 has been demonstrated to play a critical role in removing misfolded proteins from the Endoplasmic Reticulum and is implicated in severe diseases such as various cancers and Alzheimer's disease. Therefore, RHBDL4 is expected to constitute an important therapeutic target for such devastating diseases. Despite its critical role in many biological processes, the enzymatic properties of RHBDL4 remain largely unknown. To enable a comprehensive characterization of RHBDL4's kinetics, catalytic parameters, substrate specificity, and binding modality we expressed and purified recombinant RHBDL4, and employed it in a Förster Resonance Energy Transfer-based cleavage assay. Until now, kinetic studies have been limited mostly to bacterial rhomboid proteases. Our in vitro platform offers a new method for studying RHBDL4's enzymatic function and substrate preferences. Furthermore, we developed and tested potential inhibitors using our assay and successfully identified peptidyl α-ketoamide inhibitors of RHBDL4 that are highly effective against recombinant RHBDL4. We utilize ensemble docking and molecular dynamics (MD) simulations to explore the binding modality of substrate-derived peptides bound to RHBDL4. Our analysis focused on key interactions and dynamic movements within RHBDL4's active site that contributed to binding stability, offering valuable insights for optimizing the non-prime side of RHBDL4 ketoamide inhibitors. In summary, our study offers fundamental insights into RHBDL4's catalytic activities and substrate preferences, laying the foundation for downstream applications such as drug inhibitor screenings and structure-function studies, which will enable the identification of lead drug compounds for RHBDL4.
Keywords: enzyme kinetics; enzyme purification; endoplasmic-reticulum-associated protein degradation; enzyme structure; protein misfolding; enzyme inhibitor; rhomboid protease; serine protease; endoplasmic reticulum stress